Wheelchair service provision training during armed conflict: preliminary results from a pre-post study in Ukraine - Tofani, M.; Golyk, V.; Dieieva, K.; Kamadu, A.; Quinn, M. E.; Tawashy, A. E. (Frontiers in Rehabilitation Sciences, 2025)
BackgroundUniversal Health Coverage (UHC) cannot be achieved without equitable access to assistive technology (AT). Wheelchairs are among the most needed AT products worldwide, yet service provision is hindered by limited workforce capacity, inadequate training, and fragile supply systems, challenges that become critical in conflict and emergency settings.ObjectiveThis study aimed to evaluate the effectiveness of a World Health Organization (WHO)- supported wheelchair service training program in Ukraine, developed in partnership with the International Society of Wheelchair Professionals (ISWP), in improving theoretical knowledge, wheelchair skills performance and confidence, among rehabilitation professionalsMethodsA five-day, 40 h training program based on the WHO Wheelchair Service Training Package–Basic Level (WSTPb) was delivered to 39 rehabilitation professionals in Ukraine. Training combined theoretical instruction, hands-on skill practice, and adapted educational strategies, including group-based ISWP testing, to overcome infrastructure constraints. Pre- and post-training assessments were conducted using the Wheelchair Skills Test–Questionnaire (WST-Q).ResultsAll participants achieved certification in basic wheelchair service provision. Statistically significant improvements were observed in both performance (from 42.72 ± 21.89 to 68.08 ± 14.22; mean increase 25.36%) and confidence (from 40.72 ± 21.63 to 67.72 ± 12.88; mean increase 27.00%) domains of the WST-Q (p < 0.01). Importantly, rehabilitation assistants demonstrated the largest relative improvement, reducing pre-training disparities with occupational and physical therapists.ConclusionThe findings highlight how targeted educational interventions can expand the AT workforce, promote equitable skill acquisition across professional cadres, and strengthen AT integration into UHC, even in the context of armed conflict. The Ukrainian experience illustrates both the clinical challenges, such as mastering advanced wheelchair skills, and the educational challenges including addressing diverse professional backgrounds and limited infrastructure, that are inherent in AT service provision. This model can inform future workforce capacity-building strategies for AT in both emergencies and routine health system strengthening efforts.